THE EFFECT OF DEMAND AND SUPPLY ON MARKET EQUILIBRIUM IN E-COMMERCE - Aswar, Nurul Fadilah (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
The digital economic transformation has replaced conventional trading systems with an e-commerce model that is more efficient, flexible, and adaptive to market changes. This study aims to examine the influence of demand and supply variables on market equilibrium in the Indonesian e-commerce ecosystem using qualitative descriptive methods through a literature review based on secondary data from 2019 to 2024. The results indicate that digital market equilibrium is formed through direct, real-time interactions between demand and supply, driven by dynamic pricing algorithms. Consumer demand increases due to promotions, discounts, and easy access to information, while supply is adjusted based on stock availability, production costs, and pricing strategies. Price adjustments in e-commerce occur more quickly than in traditional markets due to the support of automated digital systems that maintain market stability and efficiency. These findings confirm that digitalization strengthens price elasticity and increases the efficiency of modern market mechanisms.